Prevalence of Methicillin-Resistant Staphylococcus aureus Isolated from Clinical Samples at Narayani Samudayik Hospital, Chitwan, Nepal (Tribhuvan University Journal of Microbiology, 2020)
Objectives: The main objective of this study was to determine the prevalence of Methicillin Resistance Staphylococcus aureus (MRSA) and MDR bacteria isolated from various clinical specimens from the patients attending Narayani Samudayik Hospital, ChitwanMethods: A cross sectional study was carried in NPI-Narayani Samudayik Hospital, Chitwan from June to December 2017. Altogether, 3610 clinical specimens mainly pus, blood and urine were collected, streaked on Mannitol Salt Agar and Blood Agar and incubated at 37°C for 24 hours. The confirmed colonies of S. aureus were sub-cultured on Nutrient Agar. The antibiotic susceptibility pattern of all isolates S. aureus was determined by Kirby Bauer disc diffusion method. Isolates resistant to cefoxitin (30mcg) were confirmed as MRSA.Result: Among 3610 total clinical samples, 17.6 % (635/3610) showed growth and 95(14.96%) S. aureus were isolated. Higher number of S. aureus was isolated from pus sample (93.15%). Out of 95 S. aureus isolates, 55 (57.89%) were identified as MRSA while 40 (42.10%) were MSSA. Vancomycin, ceftriaxone and chloramphenicol were found to be most effective antibiotic against isolates. Whereas, the least effective antibiotic was cefoxitin followed by amoxiclav, oxacillin and amoxicillin.Conclusion: This study concludes that the overall prevalence of MRSA and MDR among the bacterial isolates is higher compared to other studies. So, it is recommended to monitor the antibiotic susceptibility pattern of pathogens regularly and study the epidemiology of such isolates.